CFO Characteristics and Liquidity Creation: Evidence from Indonesia - Mohammed Abdullah Salem Bahbry; Tastaftiyan Risfandy; Muh. Juan Suam Toro (Journal of Management and Entrepreneurship Research, 2025)
Objective: While the importance of liquidity creation in banking has been widely acknowledged, limited empirical research has explored how Chief Financial Officer (CFO) characteristics influence this critical function, particularly within emerging markets such as Indonesia. This study addresses this gap by examining the impact of CFO attributes specifically gender, age, ethnicity, and tenure on liquidity creation in Indonesian banks. Research Design & Methods: This study adopts a quantitative research design utilizing secondary panel data from 40 banks listed on the Indonesia Stock Exchange (IDX) over the period 2013–2023. The analysis employs robust Ordinary Least Squares (OLS) regression to examine the effect of CFO characteristics including gender, age, ethnicity, and tenure on bank liquidity creation. Findings: The findings reveal that CFO age is positively associated with liquidity creation, indicating that older CFOs may be more effective in managing liquidity. Conversely, CFO gender and ethnicity exhibit significant negative effects, suggesting that female CFOs and those from minority ethnic backgrounds are linked to lower liquidity creation. CFO tenure, however, shows no statistically significant impact. Implications & Recommendations These results highlight the importance of executive demographics in shaping liquidity strategies and financial intermediation within bank-based economies. The study suggests that organizations should consider demographic diversity and experience when appointing financial leaders. Contribution & Value Added: This research adds to the limited literature on executive influence in liquidity creation, particularly in emerging markets. It offers practical insights for corporate governance, executive recruitment, and diversity policy in the financial sector.